Application of the Think Pair Share Model Assisted with the Learning CD to Improve Student Understanding Towards Pancasila Values - Achmad Dwi Cahyono; Murtono Murtono; Slamet Utomo (Peneliti.net, 2022)
The background of this research problem is the low student learning outcomes about understanding the values ​​of Pancasila in class VI of Sidomulyo 1 Elementary School, Wonosalam District, Demak Regency. This is allegedly due to the application of conventional learning models so that students do not understand the subject matter. The purpose of this study was to find an increase in understanding of Pancasila values ​​of students after the application of Think Pair Share assisted with learning CDs. This research uses a quasi-experimental method to compare the treatment of teaching and learning in the experimental class and the control class. The research design used was non equivalent pretest posttest control group design. The population studied was all grade VI students of elementary schools in Wonosalam District, Demak Regency, as many as 41 public schools. Samples in this study were taken in 3 elementary schools. which is divided into 2 classes namely control class and experimental class. The research instrument was a test consisting of 25 multiple choice questions. Data analysis techniques include instrument testing, prerequisite tests and hypothesis testing. The results of the research are that there is an increase in understanding of the values ​​of Pancasila by applying the think pair share model assisted with learning CDs in grade VI elementary schools. based on the results of t count of 5.204 then 5.204> 1, 9879 so that t count> t table. This is because think pair share learning allows students to work alone and cooperate with others, and optimize student participation and provide opportunities for students to show their participation to others. The advice given is that teachers should use the think pair share learning model and mind mapping assisted with learning CDs to improve the understanding of Pancasila values, and be able to innovate in learning